2013
DOI: 10.1186/1471-2474-14-258
|View full text |Cite
|
Sign up to set email alerts
|

An inverted J-shaped association of serum uric acid with muscle strength among Japanese adult men: a cross-sectional study

Abstract: BackgroundUric acid (UA) may protect muscle function from oxidative damage due to reactive oxygen species through its powerful antioxidant capacity. However, several studies have demonstrated that hyperuricemia is closely related to systemic inflammation and has oxidant properties effects, both of which may increase the risk of muscle strength loss. The purpose of this study was to examine the association of serum UA concentration with grip strength and leg extension power in adult men.MethodsThis study is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 41 publications
5
55
1
Order By: Relevance
“…A number of previous studies have investigated the relationship between uric acid levels and the 3 components of sarcopenia, but this is the first study to examine the 3 components (muscle mass, muscle strength, and physical performance) and the age‐related parameter, bone mineral density, in the same population. Of the 3 sarcopenia components, the correlation of uric acid to muscle mass was the strongest, for it was retained in some comparisons when uric acid quartiles were examined in both men and women, while the correlation to handgrip was only retained in one quartile comparison in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have investigated the relationship between uric acid levels and the 3 components of sarcopenia, but this is the first study to examine the 3 components (muscle mass, muscle strength, and physical performance) and the age‐related parameter, bone mineral density, in the same population. Of the 3 sarcopenia components, the correlation of uric acid to muscle mass was the strongest, for it was retained in some comparisons when uric acid quartiles were examined in both men and women, while the correlation to handgrip was only retained in one quartile comparison in men.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that increased hyperuricemia both increased and decreased muscle strength as estimated by the handgrip test. One study has associated hyperuricemia with a decrease in skeletal muscle mass .…”
Section: Introductionmentioning
confidence: 90%
“…[17,18] On the other hand, few workers have shown hyperuricemia to be associated with poor muscle strength. [19] UA was found to be significantly low in elite endurance athletes in comparison to sedentary controls. [3] Normal UA and urea levels with raised creatinine by aerobic exercises as observed in our study, rule out the presence of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 77%
“…Although, that study did not show grip strength scores being affected by gout status, another study conducted by Huang, C, et al (2013), showed the opposite. They found that participants with hyperuricemia (associated with gout) had lower grip strength scores than those without hyperuricemia (40.3 kg, 95% CI:39.2-41.3 kg versus 41.9kg, 95% CI:41.3-42.5 kg, P=0.01) and concluded that hyperuricemia is associated with poor muscle strength.…”
Section: Arthritis and Grip Strengthmentioning
confidence: 82%
“…Older adults account for 49.6% of the 54.4 million adults diagnosed and arthritis was more prevalent in women than men [24]. Arthritis also leads to pain as well as poor physical functioning in the affected joint(s) and can make various physical assessments difficult, including evaluations in grip strength [27][28][29][30][31][32] and gait speed [31,32]. Additionally, arthritis has been shown to be associated with decreases in lean mass [31,33].…”
Section: Introductionmentioning
confidence: 99%